KOMITMEN ORGANISASI GURU DILIHAT DARI PERANAN BUDAYA ORGANISASI, STRES KERJA, DAN KEPUASAN KERJA - Mulianto, Carolus Novi; Sudibjo, Niko (Jurnal Penelitian Pendidikan, 2017)
The purpose of this research is to analyze the influence of organizational culture, job stress, and job satisfaction toward organizational commitment of teacher in XYZ School. This research uses a quantitative approach with path analysis as a method to find the effect among variables. The subjects of this research are 37 teachers at XYZ School. As for the analysis of the data, SmartPLS 3.0 is used for data processing and hypothesis testing. The result of this research showed that: (1) Organizational culture has positive influence on job satisfaction, (2) job stress has negative influence on job satisfaction, and (3) Organizational culture has positive influence on organizational commitment, (2) job stress has negative influence on organizational commitment, and (3) job satisfaction has positive influence on organizational commitment.